Pectinase responsive nanoplatform for oral targeted delivery 5-aminosalicylic acid and zinc coordination driven nanozyme in inflammatory bowel disease treatment - Lin, Yiting; Fang, Siqi; Chen, Xinyi; Li, Xiang; Zhao, Xinlin; Wang, Yanwen; Lu, Jing; Ji, Qingdong; Zheng, Shuhui; Zou, Jiafeng; Qi, Chendong; Gao, Feng (International journal of pharmaceutics: X, 2025)
Characterized by weight loss, intestinal ulcerations, and diarrhea with blood or mucus, inflammatory bowel disease (IBD), which includes ulcerative colitis and Crohn's disease, is a chronic gastrointestinal condition. The rising incidence of IBD is placing pressure on healthcare systems globally. Although the precise etiology remains elusive, the dysregulation between reactive oxygen species (ROS) and hydrogen sulfide (H2S) is a crucial determinant in the pathogenesis of inflammatory bowel disease (IBD). Though 5-aminosalicylic acid (5-ASA) is effective in the early-stage of IBD, restoring intestinal environmental balance, its use is limited by off-target problem and toxicity. This study introduces a novel oral nano-drug delivery system that improves efficacy and reduces side effects by coordinating 5-ASA with Zn2+ to form nanozymes (5-ASA-Zn2+, A-Z) and encapsulating them in nanoplatform (A-Z@cHP), which made from chitosan (CS), hyaluronic acid (HA), pectin (PC) and calcium chloride. The nanozymes displayed uniform particle size, stability, and ability to regulate ROS and H2S. The nanoplatform showed the characteristic of acid resistance, pectinase responsive drug release, low cytotoxicity, and effective targeting via CD44 receptors. In a DSS-induced mouse colitis model, A-Z@cHP significantly improved body weight, disease activity index, colon length, and colonic barrier while reducing inflammation by restoring the balance of ROS and H2S. Furthermore, the balance restoration of intestinal flora also benefits from the above regulatory effect of nanoparticles. Biosafety evaluations confirmed no significant side effects. In conclusion, this targeted nanoplatform provides a promising new approach for improving the efficacy of 5-ASA against IBD. Pectinase responsive nanoplatform for oral targeted delivery 5-aminosalicylic acid and zinc coordination driven nanozyme in inflammatory bowel disease treatment. [Display omitted]